Genotype‐phenotype associations in individuals with Diamond Blackfan anaemia - D. Matthew Gianferante; Kyra J. W. Mendez; Sarah Cole; Shahinaz M. Gadalla; Blanche P. Alter; Sharon A. Savage; Neelam Giri (eJHaem)
Abstract Introduction Diamond Blackfan anaemia (DBA) is a rare disorder characterized by failure of red blood cell production, congenital abnormalities and cancer predisposition, primarily caused by pathogenic germline variants in genes encoding ribosomal proteins. Methods We conducted a genotype‐phenotype and outcome study of 121 patients with DBA spanning the 20‐year history of the National Cancer Institute's Inherited Bone Marrow Failure Syndromes study. Patient phenotypes were compared by large versus small ribosomal protein genes, across genes with >5 cases (RPS19, RPS29, RPS26 and RPL35A) and by type of pathogenic variants (hypomorphic versus null, large deletions versus others). Results A pathogenic germline variant was identified in 71% of patients (n = 86/121) from 54 families. After adjusting for multiple testing, we found that patients with RPS29 variants were least likely to need treatment for anaemia while those with large ribosomal protein subunit variants had a higher proportion of intellectual disability and gastrointestinal abnormalities compared with small ribosomal protein subunit variants (p < 3.5 × 10−4). There were no statistically significant differences in overall survival or cancer incidence among patients with large or small ribosomal subunit genes. Conclusion This detailed genotype‐phenotype study of DBA improves our understanding of the role of germline genetics in the clinical manifestations that may help guide the management of people with DBA.